Chemical Composition of Giant Rat (Cricetomys gambianus ) Found in Southwestern Nigeria - Abulude, Francis Olawale (Biological Sciences - PJSIR, 2007)
The study assessed the prox i mate composition , mi nera l contents and in vitro digesti bility of lean meat of male and female giant rat (Cricetomys gambianus) found i n th e vici ni ty ofFederal College of Agricultu re, Ak ure, Nigeria. After sacrificing and dissecting, the l ean meat was dried , ground and ch emically analyzed using standard methods. The mean wet weights of th e ma l es were 1 1 61 .2 g and females, 949. 1 g. Th e protei n content varied , ma l es h avin g 46.78% and femal es, 48.64%. The mea n (% d ry matter) fat, fibre, ash , and mo i sture con ten t were 6.38±0.79, I. I 0±0.08, 1 5.29±2.08 and 3.69±0.60, respectively. The energy content was 2.36±0. 1 1 kca l/g. The h ighly concentrated m i nera l s i n both sexes were K, Na, Ca, Mg and Fe. The digesti bi l i ty va l ue was 70% (female) and 68.25% (mal e). Biol ogical va l ue, net protei n uti l i zation and net protei n va l ue were h igher i n femal e than in male samples. Both sexes were found to h ave n utritive va l ues (protei n and mi neral s), which compared favourabl y wi th other sources of conventiona l prote i ns and m i neral s.